Кошки-мышки: [стихи для детей] / Ольга Белозерова ; [художник Анна Зобнинская] - Белозерова Ольга Александровна (Пан пресс, 2010)
Экземпляры: ф.8 (20131120) / Инвентарный номер: 55391 / Цена: / Сис.шифр: 84(2Рос-Рус)6-5 / Авт.знак: Б 43 / ГРНТИ: 17.82.93 / ББК: 84(2Рос-Рус)6-5